The Level of Bullying among Students with Learning Disabilities from the Point of View of their Parents in the City of Makkah - Alharthi, Saliha Hussein Mohammed; Abu Alula, Nawal Ahmad Elbadawy (Journal of Educational and Psychological Sciences, 2025)
The current study aimed to explore the level of bullying among students with learning disabilities (LDs) and reveal the differences in this level in light of the variables of gender, educational qualification, and chronological age from the point of view of their parents in the city of Makkah Al-Mukarramah. The researcher applied the descriptive analytical method, and the study was applied to a sample of (260) parents of people with learning disabilities using a 32 phrase questionnaire. According to the study findings, the level of bullying among students with LDs from the point of view of their parents in the city of Makkah Al-Mukarramah scored high (Avg = 3.868; relative weight = 77.36%). Verbal bullying came first, followed by social, then physical, and finally sexual bullying. The study results also revealed that there were statistically significant differences in the level of bullying among students with LDs from the point of view of their parents due to the gender variable in favor of males, the chronological age variable for the benefit of 35 to 44 year old parents and the educational qualification variable for the benefit of the higher qualification. The researcher recommended the necessity of cooperation between parents and teachers in preparing a safe classroom environment, based on building values among students. Workshops are also provided for teachers of students with learning difficulties on how to reduce bullying behavior among students. The researcher recommended the necessity of cooperation between parents and teachers in preparing a safe classroom environment, based on building values among students. Workshops are also provided for teachers of students with learning difficulties on how to reduce bullying behavior among students. The researcher recommended the necessity of cooperation between parents and teachers in preparing a safe classroom environment, based on building values among students. Workshops are also provided for teachers of students with learning difficulties on how to reduce bullying behavior among students.
Keywords: Bullying; Persons with Learning Disabilities; Parents of Students with Learning Disabilities